Introduction to the Special Issue: Islamic State’s Online Activity and Responses, 2014–2017 - Stuart Macdonald (Studies in Conflict & Terrorism, 2018)
This is the introduction to a special (double) issue of Studies in Conflict & Terrorism (volume 42, issues 1-2) that focuses on the online activities of the so-called Islamic State during the period 2014-2017 and responses to these activities. The ten papers in the special issue were all presented at the international Terrorism and Social Media Conference (#TASMConf) hosted at Swansea University in June 2017.